2019
DOI: 10.1016/j.celrep.2019.10.100
|View full text |Cite
|
Sign up to set email alerts
|

An Excitatory and Epileptogenic Effect of Dentate Gyrus Mossy Cells in a Mouse Model of Epilepsy

Abstract: SUMMARY The sparse activity of hippocampal dentate gyrus (DG) granule cells (GCs) is thought to be critical for cognition and behavior, whereas excessive DG activity may contribute to disorders such as temporal lobe epilepsy (TLE). Glutamatergic mossy cells (MCs) of the DG are potentially critical to normal and pathological functions of the DG because they can regulate GC activity through innervation of GCs or indirectly through GABAergic neurons. Here, we test the hypothesis that MC excitation of GCs is norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 100 publications
26
113
1
Order By: Relevance
“…Our data suggest facilitation can occur during trains at beta frequency (25 Hz trains) and possibly theta frequency (5 Hz trains). These observations predict that the MC-GC synapses contribute to beta-associated information processing (including memory; Kay 2014) and possibly theta-associated spatial exploration, consistent with prior studies and discussion (Soltesz et al, 1993;GoodSmith et al, 2017;Hashimotodani et al, 2017;Senzai and Buzsaki, 2017;Bui et al, 2018;Botterill et al, 2019;Jung et al, 2019).…”
Section: Insight Gained From Multiple Optogenetic Stimulisupporting
confidence: 81%
See 1 more Smart Citation
“…Our data suggest facilitation can occur during trains at beta frequency (25 Hz trains) and possibly theta frequency (5 Hz trains). These observations predict that the MC-GC synapses contribute to beta-associated information processing (including memory; Kay 2014) and possibly theta-associated spatial exploration, consistent with prior studies and discussion (Soltesz et al, 1993;GoodSmith et al, 2017;Hashimotodani et al, 2017;Senzai and Buzsaki, 2017;Bui et al, 2018;Botterill et al, 2019;Jung et al, 2019).…”
Section: Insight Gained From Multiple Optogenetic Stimulisupporting
confidence: 81%
“…During the onset of hyperexcitability accompanying acute trauma or seizures, GCs may depolarize, NMDA receptors become stronger, and GABAergic inhibition weaker or even excitatory (Lillis et al, 2012;Zhang et al, 2012). At this time, MCs appear to cause the GCs to become 'detonators' (Santhakumar et al, 2000;Botterill et al, 2019).…”
Section: When Would Weak MC Excitation Of Gcs Become Strong Enough Tomentioning
confidence: 99%
“…Importantly, electrophysiological studies from our lab (Botterill et al, 2019) and others (Yeh et al, 2018;Oh et al, 2019) have confirmed the excitatory and inhibitory effects of DREADDs in MCs. Control mice consisted of Drd2-Cre -/and Cre +/mice injected with a viral control fluorophore (mCherry).…”
Section: Experimental Design and Controlssupporting
confidence: 62%
“…To target MCs and their axons that span the septotemporal extent of the DG, virus was injected bilaterally into the rostral and caudal hippocampus as previously described (Botterill et al, 2019). Drd2-Cre +/mice were injected with eDREADDs (AAV2-hSyn-DIO-hM3D(Gq)-mCherry; ≥5x10 12 vg/mL, #44361, Addgene) or iDREADDs (AAV5-hSyn-DIO-hM4D(Gi)-mCherry; ≥8x10 12 vg/mL, #44362, Addgene; Figure 1A).…”
Section: Viral Targeting Of Mossy Cellsmentioning
confidence: 99%
See 1 more Smart Citation